2014
DOI: 10.3109/13645706.2014.955029
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian cystectomy for a dermoid cyst with the new single-port robotic system

Abstract: We report a 27 year-old patient with a dermoid cyst who underwent robotic single port transumbilical ovarian cystectomy. She was operated through a 2 cm long single midline umbilical incision using a new platform from Intuitive Surgical. The operative time was 45 minutes and the docking time was 15 minutes. Ovarian cystectomy using the da Vinci single-port system is feasible and effective. This new semi-rigid robotic surgery platform may increase access to the potential advantages of single-site surgery. Robot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…(2015) reported the largest series of robotic single‐site hysterectomies for gynecological diseases, including a total of 45 patients . Some reports showed the feasibility of single site robotic surgery in particular settings such as trans‐umbilical ovarian cystectomy or sentinel lymph node biopsy during hysterectomy in endometrial cancer with the injection of ICG into the cervical stroma . More recently Yoon et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2015) reported the largest series of robotic single‐site hysterectomies for gynecological diseases, including a total of 45 patients . Some reports showed the feasibility of single site robotic surgery in particular settings such as trans‐umbilical ovarian cystectomy or sentinel lymph node biopsy during hysterectomy in endometrial cancer with the injection of ICG into the cervical stroma . More recently Yoon et al .…”
Section: Resultsmentioning
confidence: 99%
“…Bogliolo et al (2015) reported the largest series of robotic single-site hysterectomies for gynecological diseases, including a total of 45 patients (37). Some reports showed the feasibility of single site robotic surgery in particular settings such as trans-umbilical ovarian cystectomy (38) or sentinel lymph node biopsy during hysterectomy in endometrial cancer with the injection of ICG into the cervical stroma (39). More recently Yoon et al reported that a 49-year-old patient underwent successful robotic single-port peritoneal washing, total hysterectomy, bilateral adnexectomy, and complete pelvic lymphadenectomy (40).…”
Section: Gynaecologymentioning
confidence: 99%
“…Patients benefit from smaller incisions, less postoperative discomfort, and faster recovery times. Robotic ovarian cystectomy is particularly valuable for preserving ovarian function in cases where cyst removal is required [22].…”
Section: Gynecological Surgerymentioning
confidence: 99%
“…Single-site robotic surgeries are a particularly promising application for benign adnexal masses (see section on single-site robotics). 49,50 Endometriosis Deep infiltrating endometriosis (DIE) is a complex and surgically challenging process. It occurs in approximately 30% of women with endometriosis and can involve the uterosacral ligaments, bowel (most commonly rectum and rectosigmoid colon), bladder, vagina, and ovaries.…”
Section: Benign Adnexal Massesmentioning
confidence: 99%